2009
DOI: 10.2466/pr0.105.2.375-380
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Anger and Paranoid Thoughts in a Nonclinical Sample

Abstract: Anger has been suggested to be associated with paranoid thoughts in nonclinical groups. For a clear evaluation of the relationship between anger and paranoid thoughts, successive preliminary surveys were conducted in a student group in Japan. A total of 102 undergraduate students completed two scales-the Paranoia Checklist and the Spielberger Trait Anger Expression Inventory. The participants filled out the questionnaires twice, at a 1-mo. interval. The synchronous effects model was used to examine the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…On the Paranoia Checklist, 37% of the sample showed frequency, degree of conviction, and distress paranoid thoughts (M = 35.50, SD = 7.21). The Cronbach's α for the Paranoia Checklist was .87, indicating good reliability, consistent with research in other countries (e.g., Brown, 2010;Barreto Carvalho et al, 2018;Freeman, Garety, Bebbington, Smith, et al, 2005;Hirao, 2016;Yamauchi et al, 2007Yamauchi et al, , 2009aYamauchi, Sudo, & Tanno, 2009c;.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the Paranoia Checklist, 37% of the sample showed frequency, degree of conviction, and distress paranoid thoughts (M = 35.50, SD = 7.21). The Cronbach's α for the Paranoia Checklist was .87, indicating good reliability, consistent with research in other countries (e.g., Brown, 2010;Barreto Carvalho et al, 2018;Freeman, Garety, Bebbington, Smith, et al, 2005;Hirao, 2016;Yamauchi et al, 2007Yamauchi et al, , 2009aYamauchi, Sudo, & Tanno, 2009c;.…”
Section: Discussionsupporting
confidence: 86%
“…The results are consistent with other studies, for example, Yamauchi et al (2007) indicated that the Japanese-version Paranoia Checklist (JPC) scores positively correlated with the Paranoia Scale and the Peters et al Delusions Inventory (PDI). In two studies, Yamauchi et al (2009a) found that the Paranoia Checklist correlated with the Spielberger Trait Anger Expression Inventory in undergraduate students, and Yamauchi et al (2009c) showed that the JPC positively correlated with trait anxiety, social anxiety, and anger, and negatively correlated with social support. reported that the Paranoia Checklist correlated .52 with the Positive and Negative Syndrome Scale (PNSS).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, people with psychosis might also experience difficulties in regulating other distressing emotions. Some studies found that anger was related to or even predicted paranoia (Thewissen et al ., ; Yamauchi, Sudo, & Tanno, ). Furthermore, high levels of shame have been shown to be the characteristic of persons within the post‐psychotic recovery phase (Michail & Birchwood, ; Turner et al ., ).…”
Section: Introductionmentioning
confidence: 99%